Using the Qris Bri Mobile Payment Method to Increase Profitability of MSMEs - Anidya Ilmi Febriyanti; Mochammad Isa Anshori (PT FORMOSA CENDEKIA GLOBAL, 2024)
Electronic money and QRIS (Quick Response Code Indonesia Standard) are digital payment tools that are increasingly popular in Indonesia. Electronic money, stored in digital form on a chip or server, facilitates transactions with greater speed and convenience than cash. QRIS, introduced by Bank Indonesia, unites various digital wallet applications in one QR code, making it easier for merchants to accept payments from various digital platforms. QRIS BRI Mobile, an innovation from Bank BRI, supports MSME profitability by expanding markets, increasing efficiency, transparency and reducing operational costs. The implementation of QRIS BRI Mobile not only helps MSMEs increase efficiency and reduce operational costs, but also opens up new opportunities to increase revenue and profitability. The suggestions from this research are to increase education and socialization of the use of electronic money and QRIS to the public, as well as encouraging the development of security features and ease of transactions by banks and payment service providers. Apart from that, adaptive regulations that support innovation from the government and related institutions are also needed to encourage economic growth and financial inclusion in Indonesia.